Environnement politique et réglementaire des pharmacultures au Canada : la contamination pharmaceutique à l’horizon ? - Marie-Hélène Bacon (VertigO)
During the years 1980’s, the Canadian government decided to stimulate the development of biotechnologies in order to become a leader in this sector. Since then, many policies as well as regulatory and financial initiatives have been designed by the government to achieve that goal. As a result, Canada is today among the firsts countries in the world in terms of hectares of genetically modified (GM) crops. Within these multiple fields of GM crops grows, since 1994, transgenic plants which could eventually produce pharmaceutical molecules.  Called pharma-crops, these new genetically modified organisms (GMO) could, among many other things, contaminate the food system and the environment. We have learned from recent events related to GM crops that in the actual scientific and regulatory context, no biological, physical or political limits seems to be able to contain effectively transgenic contamination. As such, pharma-crops could generate health, environmental and socioeconomic impacts which would spread beyond the Canadian territory.Despite that, the Canadian government and his regulatory agencies such as the Canadian Food Inspection Agency maintain that they can, at the same time, stimulate economical grow and protect the population’s health and the environment. The analysis of the policies and regulations in Canada underline that the economical goal actually  jeopardise the regulatory  process and the scientific evaluation of pharma-crops and thus, put at stake the protection of the populations and the environment.